Design entropy theory: A new design methodology for smart PSS development. (August 2020) - Cong, Jingchen; Chen, Chun-Hsien; Zheng, Pai
Abstract: Smart product-service systems (Smart PSS), as an emerging digital servitization paradigm, leverages smart, connected products and their generated services as a solution bundle to meet individual customer needs. Owing to the advanced information and communication technologies, Smart PSS development differs from the existing product and/or service design mainly in three aspects: (1) closed-loop design/redesign iteration; (2) value co-creation in the context; and (3) design with context-awareness. These unique characteristics bring up new design challenges, and to the authors' best knowledge, none of the existing design theories can address them well. Aiming to fill this gap, a novel design methodology for the Smart PSS development is proposed based on the information theory, where both the system and stakeholders can be regarded as the information containers. Hence, the closed-loop design/redesign iteration can be treated as the dynamic change of information and entropy in a balanced ecosystem. Meanwhile, the value co-creation process is considered as the exchange of accumulated information via the container. Lastly, the design context-awareness represents the process of reducing entropy. As a novel prescriptive design theory, it follows Shannon's information theory to determine the best design/redesign solutions by considering the three characteristics integrally. It is hoped that the proposed design entropy theory can largely facilitate today's Smart PSS development with better performance and user satisfaction.